The value of IN novative ICT guided disease management combined with T elemonitoring in OU tpatient clinics for C hronic H eart failure patients. Design and methodology of the IN TOUCH study: a multicenter randomised trial - van Dijk Rene B; Jaarsma Tiny; van der Wal Martje HL; de Jong Richard M; de Vries Arjen E; Hillege Hans L (BMC, 2011)
Abstract Background Although the value of telemonitoring in heart failure patients is increasingly studied, little is known about the value of the separate components of telehealth: ICT guided disease management and telemonitoring. The aim of this study is to investigate the value of telemonitoring added to ICT guided disease management (DM) on the quality and efficiency of care in patients with chronic heart failure (CHF) after a hospitalisation. Methods/Design The study is divided in two arms; a control arm (DM) and an intervention arm (DM+TM) in 10 hospitals in the Netherlands. In total 220 patients will be included after worsening of CHF (DM: N = 90, DM+TM: N = 130). Total follow-up will be 9 months. Data will be collected at inclusion and then after 2 weeks, 4.5 and 9 months. The primary endpoint of this study is a composite score of: 1: death from any cause during the follow-up of the study, 2: first readmission for HF and 3: change in quality of life compared to baseline, assessed by the Minnesota Living with Heart failure Questionnaire. The study has started in December 2009 and results are expected in 2012. Conclusions The IN TOUCH study is the first to investigate the effect of telemonitoring on top of ICT guided DM on the quality and efficiency of care in patients with worsening HF and will use a composite score as its primary endpoint. Trial registration Netherlands Trial Register (NTR): NTR1898